Egypt - Heinrichs, Ann. (New York : Children's Press, 2012)
Describes the geography, plants, animals, history, economy, language, religions, culture, sports, arts, and people of Egypt.
Children of the revolution -- Black land, red land -- Nature in the desert -- From pharaohs to presidents -- Governing the nation -- Making a living -- Crowded cities, common bonds -- Spiritual lives -- Culture and fun -- Many flavors of life.
Includes bibliographical references and index.
Keywords: Egypt -- Juvenile literature